Efektivitas Pelaksanaan Program Pemutihan Pajak Kendaraan Bermotor Di Provinsi Riau - Andre Dwijaya Taufiq; Zulkarnain Zulkarnain (Jurnal Media Administrasi, 2024)
There are many taxpayers who have not paid their motor vehicle tax, even though the aim of the motor vehicle tax reduction program in Riau Province is so that taxpayers pay their motor vehicle tax after the tax payment period has passed. This research aims to see how effectively the motor vehicle tax reduction program in Riau Province has been running. The research method this time is using a qualitative research method. The reason the researcher used a qualitative research method was so that the researcher could see and analyze the extent to which the effectiveness of the motor vehicle tax reduction program in Riau Province was running. The theory in this research uses Mahmudi's effectiveness theory which consists of quality, quantity and time. The results of this research are that the motor vehicle tax whitening program that is already underway in Riau Province cannot be said to be effective. According to calculations, the number of vehicles that are in arrears in their motor vehicle tax payments is around 1 million vehicles and so far those who have utilized the motor vehicle tax whitening program in Riau Province are around 390 thousand motor vehicles. With this number of vehicles, researchers can conclude that less than half of the number of motorized vehicles in Riau Province have paid their motor vehicle tax which is in arrears. Of course, the hope is that the vehicle tax reduction program in Riau Province can make people aware of their tax obligations, where this program also exists to relieve people because they no longer need to pay administrative tax fines, they just have to pay the principal tax.